Different methylation and MicroRNA expression pattern in male and female familial breast cancer1. Issue 6 (25th February 2013) - Pinto, Rosamaria; Pilato, Brunella; Ottini, Laura; Lambo, Rossana; Simone, Giovanni; Paradiso, Angelo; Tommasi, Stefania
Abstract Epigenetic regulation, has been very scarcely explored in familial breast cancer (BC). In the present study RASSF1A and RAR beta promoter methylation and miR17, miR21, miR 124, and let‐7a expression were investigated to highlight possible differences of epigenetic regulation between male and female familial BC, also in comparison with sporadic BC. These epigenetic alterations were studied in 56 familial BC patients (27 males and 29 females) and in 16 female sporadic cases. RASSF1A resulted more frequently methylated in men than women (76% vs. 28%, respectively, P = 0.0001), while miR17 and let‐7a expression frequency was higher in women than in men (miR17: 66% in women vs. 41% in men, P < 0.05; let‐7a: 45% in women vs. 15% in men, P = 0.015). RASSF1A methylation affected 27.6% of familial BC while 83% of familial cases showed high expression of the gene (P = 0.025); on the contrary, only 17% of familial BC presented RAR beta methylation and 55% of familial cases overexpressed this gene (P = 0.005). Moreover, miR17, miR21, and let‐7a resulted significantly overexpressed in familial compared to sporadic BC. RASSF1A overexpression (86% vs. 65%, P = 0.13) and RAR beta overexpression (57% vs. 32%, P = 0.11) were higher in BRCA1/2 carriers even if not statistical significance was reached. BRCA mutation carriers also demonstrated significant overexpression of: miR17 (93% vs. 35%, P = 0.0001), let‐7a (64% vs. 16%, P = 0.002), and of miR21 (100% vs. 65%, P = 0.008). In conclusion, the present data suggest the involvement of RASSF1A in familial male BC, while miR17 and let‐7a seem to be implied in familial female BC. J. Cell. Physiol. 228: 1264–1269, 2013. © 2012 Wiley Periodicals, Inc.